Comparison of the Effectiveness of Permethrin 1% and Dimeticone 4% as Therapy of Pediculosis Capitis: Literature Review - Herdiyanti, Dwi Advina; Dewi, Listiana Masyita; Aisyah, Riandini (Prosiding University Research Colloquium, 2022)
Background: Pediculosis capitis is a scalp disease caused by the infestation of obligate ectoparasites. Infection is usually found in children aged 6-12 years, girls have a higher risk of infection than boys, especially in rural areas in developing countries. One example of treatment that can be done to treat Pediculosis capitis infection is the use of 1% permethrin or 4% dimeticone. Objective: The aim of this study was to compare the effectiveness of permethrin 1% and dimeticone 4% as a treatment for pediculosis capitis. Methods: The research method uses a literature review research design. The data in this study were obtained from several journal databases, namely PubMed, Google Scholar, and Research Gate with the keywords "Permethrin 1%" AND "dimeticone 4%" AND "pediculosis capitis". The data analysis method in this study uses the critical appraisal method with a search strategy in the form of PICO (Population, Intervention, Comparation, Outcome). Results: The results of this study concluded that the use of 4% dimeticone was more effective when compared to the use of 1% permethrin as a treatment for pediculosis capitis.